Os Warao e a interculturalidade: propostas para uma educação escolar indígena migrante a partir da ACP/Roraima - Soares, Valclécia Bezerra (2022)
Since 2014, Brazil has experienced the arrival of Venezuelan indigenous groups. The flow begins to intensify in 2016 and the largest number corresponds to indigenous people of the Warao ethnic group, coming from the delta of the Orinoco River, in the Northeast region of Venezuela. The border through which they enter the country is located in the municipality of Pacaraima/RR. Upon arriving in Brazil, part of these groups move to other regions of the country, but the state of Roraima continues to have a strong presence of indigenous Venezuelans, whether from new groups that arrive or from groups that remain in the state since their arrival. The permanence of these groups arouses several discussions and the number of children and adolescents of compulsory school age who were not being attended led to the filing of a Public Civil Action (ACP) in 2018, brought by the Federal Public Ministry, whose defendants are the Federal Government, Funai, the State of Roraima and the municipalities of Boa Vista/RR and Pacaraima/RR. The ACP's objective is to make the defendants adopt the necessary measures to offer school education to the Venezuelan indigenous peoples residing in Roraima. In this dissertation, I seek to understand how school attendance for indigenous Venezuelans is thought, from the positions of the social actors involved, present in the documents that make up the ACP-Warao/RR, based on the analysis of normative documents of indigenous school education in Venezuela and Brazil to understand how it is discussed in both contexts and the main advances of differentiated school education and application of the principle of interculturality, so discussed in recent decades. The ACP-Warao/RR was filed in 2018 with a request for injunctive relief, which was intended to ensure that indigenous Venezuelans were included in education systems even before the process came to an end. However, Over the nearly four years of the process analyzed in the present work, what became evident was the slowness, the lack of articulation and political will, through a series of justifications, such as the lack of legal provisions, financial resources, trained professionals , physical structure, legal competence of the defendants, among others that, instead of solving the problem, made the non-attendance to be continually updated.